Influence of Rainfall Conditions on Stability of Slope Reinforced by Polymer Anti-slide Pile - Wang, Yuke; Han, Musen; Lin, Xiaoying; Li, Dongbiao; Yu, Hongliang; Zhu, Lei (Frontiers in Earth Science, 2021)
Traditional reinforced concrete piles have high strength and low cost in slop engineering, but the slow forming and long maintenance period make it difficult to meet the needs of emergency and disaster relief tasks, such as landslide disasters of slop caused by rainfall. In this paper, the influence of a new type of polymer anti-slide pile on slope stability under rainfall conditions is studied. With the advantages of fast forming, high strength, simple construction technology and small disturbance to slope, the new type of anti-slide pile can meet the requirements of emergency and disaster relief tasks. The influence of different rainfall time, rainfall form, location and spacing of pile laying on stability of rainfall slope is explored with fluid-solid coupling analysis. The results show that the slope stability gradually deteriorates with the increase of the peak duration of rainfall intensity. Without rainfall conditions, the reinforcement effect is the optimal when the position of pile cloth is 1/2-3/4L away from the foot of the slope (L is the horizontal length of the slope); with rainfall conditions, when the position of pile cloth is 1/4-1/2L away from the foot of the slope, the reinforcement effect is the optimal. Without rainfall conditions, the reduction of pile spacing can improve the reinforcement effect; with rainfall conditions, the reduction of pile spacing will affect the flow and discharge of seepage rainwater and reduce the reinforcement effect.